Current Views on the Pathogenesis and Principles of External Treatment of Atopic Dermatitis in Children - Nikolay N. Murashkin; Alexander I. Materikin; Eduard T. Ambarchyan; Roman V. Epishev ("Paediatrician" Publishers LLC, 2016)
The article analyzes the current data on the pathogenesis of atopic dermatitis. It discusses the role of the damaged dermal barrier structure in the development of food allergies and presents the results confirming the theory of transdermal sensibilisation to allergens in addition to hereditary and exogenous factors. Current local treatment of atopic dermatitis using topical glucocorticosteroids (tGCs) aimed at reducing the severity of symptoms is often associated with the risk of complications. The data on the effective use of topical calcineurin inhibitors (TCI) to eliminate the side effects of tGCs are presented. The results of the possible use of pimecrolimus in the form of 1% cream for gradual withdrawal of tGCs in the long-term use are shown. The data of reviews and meta-analyses for the last decade are given showing that there is no evidence that the use of TIC is associated with an increased risk of lymphoma. The authors conclude that pimecrolimus in the form of 1% cream is the best medication for topical therapy in children with mild and moderate form of the disease. It is also considered the best preparation for the proactive treatment of atopic dermatitis in the long period of time in order to prevent recurrences.